2010
DOI: 10.2174/1874848101003010010
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Evaluation of the Safety, Efficacy and Purity of VigRX, an Herbal Combination Formula, for the Enhancement of Male Sexual Health~!2009-12-10~!2010-03-04~!2010-03-31~!

Abstract: An herbal combination formula, known as VigRX, has been studied for purity, safety and for efficacy in a Sprague-Dawley rat model. Two separate assays determined that VigRX was free from pharmaceutical adulterants, including phosphodiesterase type 5 (PDE-5) inhibitors and related analogues. An in vitro assay determined that VigRX is able to inhibit the enzyme Rho-kinase, suggesting a potential mechanism of action for this product. A 2-week (14-day) study in rats demonstrated a marked enhancement in sexual beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In the present study, any observed increase in sperm parameters could also be attributed to cAMP and cGMP specific PDE inhibition. Another hypothesis for increase in sperm count by MEBF and sildenafil treatment is that these pharmacological agents increase blood flow to testes and consequently increase spermatogenesis [40]. …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, any observed increase in sperm parameters could also be attributed to cAMP and cGMP specific PDE inhibition. Another hypothesis for increase in sperm count by MEBF and sildenafil treatment is that these pharmacological agents increase blood flow to testes and consequently increase spermatogenesis [40]. …”
Section: Discussionmentioning
confidence: 99%
“…Development of this product was based on the preliminary evaluation of a first generation product, VigRX, consisting of a proprietary blend of Panax ginseng Serenoa repens Gingko biloba Crataegus laevigata Ptychopetalum olacoides Erythroxylum catuaba Cuscuta chinensis , and Epimedium sagittatum extract. In two different studies in male Sprague–Dawley rats, VigRX was shown to engender a marked improvement in sexual behaviour including decreased intromission and ejaculation latencies, and increased intromission, ejaculation and mounting frequencies [ 11 ]. In the same study, assays for pharmaceutical adulteration found that VigRX did not contain any detectable levels of known PDE-5 inhibitors including sildenafil, tadalafil, vardenafil or related analogues.…”
Section: Introductionmentioning
confidence: 99%